Width Design of Small Coal Pillar of Gob-Side Entry Driving in Soft Rock Working Face and Its Application of Zaoquan Coal Mine - Ai Chen (Advances in Civil Engineering)
Reasonable width of gob-side coal pillar can reduce the waste of coal resources and is conducive to roadway stability. According to the distribution of internal and external stress fields at the working face, a method for determining the width of gob-side coal pillar was proposed. The coal pillar and roadway should be set within the internal stress field, and support is provided through the anchored part and the intact part of the coal pillar. The method was used in the design of the coal pillar at No. 130205 working face of Zaoquan Coal Mine. The calculation results indicated that the width of a coal pillar suitable for gob-side entry is 6.0 m. It is reasonable to arrange the roadway and coal pillar in the low-stress zone with a width of 11 m. During tunnelling of roadway and stoping of the working face, the deformation of the roadway increased with a reduction in the distance from the working face. Even during stoping of the working face, there was an approximately 1.5 m intact zone in the coal pillar. This indicates that the proposed method of designing small coal pillar of gob-side entry driving is reliable.